High Speed Railway Track Dynamics Models, Algorithms and Applications - Lei, Xiaoyan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book systematically summarizes the latest research findings on high-speed railway track dynamics, made by the author and his research team over the past decade. It explores cutting-edge issues concerning the basic theory of high-speed railways, covering the dynamic theories, models, algorithms and engineering applications of the high-speed train and track coupling system. Presenting original concepts, systematic theories and advanced algorithms, the book places great emphasis on the precision and completeness of its content. The chapters are interrelated yet largely self-contained, allowing readers to either read through the book as a whole or focus on specific topics. It also combines theories with practice to effectively introduce readers to the latest research findings and developments in high-speed railway track dynamics. It offers a valuable resource for researchers, postgraduates and engineers in the fields of civil engineering, transportation, highway &railway engineering.
Track dynamics research contents and related standards -- Analytic method for dynamic analysis of the track structure -- Fourier transform method for dynamic analysis of the track structure -- Analysis of vibration behavior of the elevated track structure -- Track irregularity power spectrum and numerical simulation -- Model for vertical dynamic analysis of the vehicle-track coupling system -- A cross iteration algorithm for vehicle-track coupling vibration analysis -- Moving element model and its algorithm -- Model and Algorithm for Track Element and Vehicle Element -- Dynamic Analysis of the Vehicle-Track Coupling System with Finite Elements in a Moving Frame of Reference -- Model for vertical dynamic analysis of the vehicle-track-subgrade-ground coupling system -- Analysis of Dynamic Behavior of the Train - Ballast Track - Subgrade Coupling System -- Analysis of Dynamic Behavior of the Train - Slab Track - Subgrade Coupling System -- Analysis of dynamic behavior of the transition section betweenballast track and ballastless track -- Environmental vibration analysis induced by overlapping subways.
Keywords: Transportation engineering; Traffic engineering; Multibody systems; Vibration; Mechanics, Applied; Nonlinear Optics; Engineering mathematics; Engineering -- Data processing; Transportation Technology and Traffic Engineering; Multibody Systems and Mechanical Vibrations; Nonlinear Optics; Mathematical and Computational Engineering Applications